In-vitro digestibility, protein digestibility corrected amino acid, and sensory properties of banana-cassava gluten-free pasta with soy protein isolate and egg white protein addition - Adetiya Rachman; Margaret A. Brennan; James Morton; Damir Torrico; Charles S. Brennan (Food Science and Human Wellness)
Soy protein isolate and egg white protein were added to cassava-banana gluten-free pasta and the effects on the nutritional quality, digestibility properties, protein digestibility corrected amino acid (PDCAA), and sensory acceptance of the pasta was observed. Banana-cassava composite flour (75:25) was blended with soy protein isolate or egg white protein at the following rates: 0, 5, 10, and 15 g/100 g flour. Cooked pasta samples were analysed for total phenolic content (TPC), antioxidant activity, amino acid profiles, protein content, starch digestibility, protein digestibility and protein digestibility corrected amino acid score (PDCAAS). Addition of both proteins decreased starch digestibility, increased protein digestibility, improved the balance of the amino acid profile, and PDCAAS whereas only soy protein isolate enhanced the TPC and antioxidant capacity of the banana-cassava pasta. An egg white protein-fortified banana-cassava pasta had better customer acceptance and purchase intent than soy protein isolate inclusion.